2009
DOI: 10.3844/ajas.2009.902.912
|View full text |Cite
|
Sign up to set email alerts
|

The First Report of the Occurrence of Anthracnose Disease Caused by Colletotrichum gloeosporioides (Penz.) Penz. & Sacc. on Dragon Fruit (Hylocereus spp.) in Peninsular Malaysia

Abstract: Problem statement:The increasing of dragon fruit (Hylocereus spp.) plantations in Malaysia enhances the researches on this crop, particularly focusing on its physico-chemical characteristics, great potential health benefits and nutritional value. However, its scientific report of disease is still lacking, primarily on anthracnose disease. This study was then conducted to investigate the distribution of anthracnose disease on dragon fruit and to correlate its occurrence with weather and cultural data. Approach:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 5 publications
0
9
0
1
Order By: Relevance
“…This ubiquitous fungal spp. is responsible for anthracnose of different tropical fruits such as banana, papaya and dragon fruits caused by C. musae and C. gloeosporioides, respectively (Ranasinghe et al 2002;Bautista-Baños et al 2003;Masyahit et al 2009). Anthracnose can affect fruits at early stages of development in the field and also damage mature fruits during storage.…”
Section: Introductionmentioning
confidence: 99%
“…This ubiquitous fungal spp. is responsible for anthracnose of different tropical fruits such as banana, papaya and dragon fruits caused by C. musae and C. gloeosporioides, respectively (Ranasinghe et al 2002;Bautista-Baños et al 2003;Masyahit et al 2009). Anthracnose can affect fruits at early stages of development in the field and also damage mature fruits during storage.…”
Section: Introductionmentioning
confidence: 99%
“…Colletotrichum is a fungal genus comprising a large number of endophytic, saprophytic, and plant pathogenic species. It is one of the most economically important plant pathogenic genera that causes anthracnose disease of fruits and leaves in a wide range of hosts, resulting in severe crop reduction and conspicuous postharvest losses of tropical and subtropical cereals, grasses, legumes, vegetables, and tree fruits. For this reason species belonging to this genus have been the subject of extensive studies involving their pathogenesis, morphology, multigene analysis, physiology, host range, and disease life cycle. However, because of the large size of the genus, the production of secondary metabolites by various species is only partially explored (for a review, see Carcía-Paión and Collado, 2003) .…”
mentioning
confidence: 99%
“…Higher temperature and higher humidity generally play important role for infection and anthracnose disease development. Masyahit et al (2009) reported that temperature from 26.5 to 28.1°C and relative humidity from 77.5 to 86.6% favour the infection and disease development of anthracnose of dragon fruit (Hylocereus spp.) in Peninsular Malaysia.…”
Section: Resultsmentioning
confidence: 99%
“…One of the most severe fungal diseases of H. polyrhizus is anthracnose which can reduce production (Crane and Balerdi 2009;Masyahit et al 2009). During a disease survey of fungal diseases associated with H. polyrhizus, anthracnose symptoms were observed on the stems of H. polyrhizus in the states of Kedah and Penang, Peninsular Malaysia in August 2010 and January 2011, respectively.…”
Section: Introductionmentioning
confidence: 99%